PENGARUH TEKANAN KETAATAN, TEKANAN ANGGARAN WAKTU, PENGALAMAN AUDITOR DAN SELF EFFICACY TERHADAP AUDIT JUDGMENT (Studi Kasus pada KAP di Kota Pekanbaru, Batam dan Medan) - Diva Dwi Andani; Amir Hasan; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to examine the effect of obedience pressure, time budget pressure, auditor experience and self efficacy to audit judgment was taken by auditor. Audit judgment is used in order to produce the final opinions about the fairness of a company’s financial statement to be issued by the auditor. The quality produced by the auditor judgement may be interrupted because of a situationthat occurred in the ethical dilemma that will affect the auditor’s take an ethical decision that will affect the resulting judgment. Accuracy auditor to generate audit judgment influenced by obedience pressure, time budget pressure, auditor experience and self efficacy .The study population was all auditor who worked on the firm in Pekanbaru City, Batam City, and Medan City, and has worked at least 2 year experience. Sampling was done using a simple sampling to obtain as many as 160 respondents. The data used in this study is primary data in the form of a questionnaire. From 160 questionnaires has distributed, only 130 questionnaires can be processed. The result of this research is indicating that obedience pressure, time budget pressure, auditor experience and self efficacy effects on audit judgment with significance level of 6%, 0%, 0% and 0%.Keywords : audit judgment, obedience pressure, time budget pressure, auditor experience, self efficacy